Nyckeltal för älg och fodertillgång på tall Pinus sylvestris och rönn Sorbus aucuparia - Åkerblom Andersson, Mikael (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2014)
It has been shown that moose can affect plant community composition and structure. Selective browsing with other damages of large herbivores on tree species with different tolerance to disturbance could reshape the tree layer in both managed and natural forests. Rowan Sorbus aucuparia is widely distributed throughout Sweden and Europe. Research has shown that browsing by moose may prevent rowan from reaching browsing safe heights. The goal has been formulated that, where rowan is indigenous, it should have a good competition status and be able to reach tree level. This thesis examines occurrence and height over a 10 year period for rowan abundance and height in five moose management areas in Västerbotten County in Sweden. What is the relationship between moose population density and abundance and height of rowan? An investigation of the inventory methodology used today for rowan abundance in ÄBIN (Method for estimating browsing damage) was also included. The study shows a significant correlation between rowan height and rowan abundance, and number of fresh damage to pine. Moose density and rowan abundance has declined over the period, while rowan height has increased. The current survey method for rowan abundance systematic underestimates the abundance of rowan in a landscape perspective. For rowan to become tree forming, it requires active measures like rowan plant protection and active wildlife management.